Zgodnja dela Antona Tomaža Linharta - Kos, Janko (Slavistična revija, 2007)
Linhart's early poetry (Blumen aus Krain) and drama (Miss Jenny Love), both in German, received considerable attention from scholars only in recent decades. The article examines the findings of this research and on this basis treats the open questions, i.e., what poetic or dramatic traditions Linhart's early works follow, why Linhart gave up writing original poetry and drama, and what the meaning of these works is for his later dramatic and theatrical production, in particular for his adaptation of foreign theater pieces for Slovene theater.
Keywords: 18. st.; Age of Enlightenment; Blumen aus Krain; drama; dramatika; Linhart, Anton Tomaž, 1756-1795; literarne študije; Miss Jenny Love; poezija; prevodi v slovenščino; priredbe dramskih besedil; razsvetljenski sentimentalizem; razsvetljenstvo; Slovene literature; slovenska književnost; viharništvo